Analgesia for patients with advanced disease: 2. Issue 942 (13th April 2004) - Hall, E J; Sykes, N P
Abstract : The first article in this series explored epidemiology and patterns of pain in advanced disease, non-pharmacological treatments, and the use of opioids to manage pain. This second article examines the use of non-opioid drugs and anaesthetic interventions for pain relief in advanced disease. It also discusses an approach to managing analgesia in dying patients and finally looks at future developments.